(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
It is substantiated that an important condition for the sustainable functioning of the tax system and the national economy as a whole is effective tax administration, which contributes to the growth of tax revenues through compliance with tax discipline by taxpayers and prevention of violations of tax legislation. The essence and features of tax administration are studied, the factors of influence are defined and its main functions are characterized, which include: tax planning and forecasting, taxpayers’ and objects of taxation’ accounting, tax analysis, tax control, tax regulation, tax consulting. It is established that the purpose of tax administration is to ensure timely receipt of tax payments in full to the budget in compliance with the set of principles defined by the Tax Code of Ukraine, including the principle of cost-effectiveness of taxation, when the cost of administration of taxes and fees should be much less than revenues from their payment. It is proved that effective tax administration is determined primarily by the establishment of partnerships between tax authorities and taxpayers. This approach is ensured through the maximum implementation of the incentive function of taxes, by reaching an agreement and compromise between taxpayers and the state, in compliance with the principles of honesty and legality in tax relations. The necessity of automation of all procedures of tax administration due to introduction of modern information technologies that will promote openness of tax relations and optimization of expenses for calculation and payment of tax payments is shown. The Strategic goals of the State Tax Service of Ukraine until 2022 are given, special attention should be paid to ensuring the effective administration of taxes, fees and charges. The achievement of target values ​​of key indicators of efficiency of tax administration within the framework of realization of the specified Strategy is considered and increase of efficiency of control procedures of its bodies is revealed. The achievement of target values ​​of key indicators of efficiency of tax administration within the framework of implementation of the mentioned Strategy is considered and the increase of efficiency of control procedures of its bodies is revealed, in particular due to growth of actual share of accrued sums of monetary obligations under taxes, overfulfillment according to indicative indicators.